THE CITY AS A STAGE OF THE DEMONIC IN BULATOVIĆ’S NOVEL PEOPLE WITH FOUR FINGERS (Heritage, 2025)
In the paper, using the example of Bulatović’s award-winning novel People with Four Fingers, the relationship of the contemporary author to the phenomenon of the city is critically examined. First, Voltaire's Enlightenment theses about the significance of the city as the epicenter of reason and ethical purity are established, only to be completely abandoned and deconstructed in the literature of the 19th and 20th centuries. Bulatović's implicit portrayal of the city is particularly examined – the image of German cities is formed through key and darkest spaces in urban environments (train stations, trains, garbage dumps, brothels, taverns). The carnivalistic underpinnings on which the narrative is built are also explored, as well as the hidden mythological and traditional elements from which it is constructed. Analyzing key novelistic toponyms (the city of Cirndorf, the train station, Drakulina Plateau, and the Gross-Lipen garbage dump), the conclusion is drawn that in Bulatović’s novel, the city represents a stage ruled by a demonic world – not so different from the dehumanized and animalized bourgeois (especially immigrant) world.
Keywords: Miodrag Bulatović, People with Four Fingers, city, demonic world, toponym.